Penerapan Project Based Learning untuk Meningkatkan Motivasi Belajar Matematika - Dyana Indri Hapsari; Gamaliel Septian Airlanda; Susiani Susiani (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve the motivation to learn mathematics through the application of project based learning (PjBL) models for the fiffth grade students. The PjBL learning model is a contextual learning model using projects as media so that it is expected to change the way students learn independently by increasing the learning motivation and creativity of students. This research is an action research which consists of two cycles. The results showed that the PjBL learning model was carried out by steps; a) find basic questions, b) compile project plans, c) compile and carry out project activities, d) monitor project progress, e) assess project outcomes, f) evaluate experience. In this study it was found that the PjBL model has been shown to increase mathematics learning motivation by 8%, ie 75% in cycle 1 and increased 83% in cycle 2. Based on the results of the study, the implementation of project based learning can increase motivation to learn mathematics. Therefore, project based learning is recommended to be applied in mathematics learning.